How to repair an immediately post-operative anterior cruciate ligament reconstruction failure? About a clinical case - Estves, Joao; Rosa, Joao Maia; Barros, Luis; Ribau, Ana; Pereira, Paulo; Vilaça, Adelio (International Journal of Research in Orthopaedics, 2019)
We present a 23-year-old male with an early anterior cruciate ligament (ACL) reconstruction failure due to lateral wall blow-out, diagnosed on day one post-op. We were able to perform the revision using the original graft, and maintaining the initial tibial fixation, revising only the femoral fixation. At 1-year follow-up the patient is asymptomatic. In the early ACL reconstruction failures due to femoral wall blowout, it is possible to perform the revision surgery using the same graft and maintaining the same tibial fixation. This avoids de morbidity of a new graft harvest and the need for a new tibial tunnel.